The Influence Of Room Rates And Facilities On Guest Decisions To Stay At The Aveda Boutique Hotel Petitenget Bali - Noviantini Jehabu, Florentina; Wisnawa, I Made Bayu; Kristiana Putri, Komang Shintiya Nita; Rusmiati, Ni Nyoman; Arini, Ni Nyoman (Akademi Komunitas MAPINDO, 2023)
This study aims to determine the partial and simultaneous effects of Room Prices, and Facilities on Guest Stay Decisions at The Aveda Boutique Hotel. This study uses data collection techniques in questionnaires, interviews and documentation. This type of research is a type of quantitative research. The population in this study were guests staying at The Aveda Boutique Hotel using the Accidental Sampling sampling technique with 75 respondents. This study uses a quantitative method with SPSS (Statistical Package For Social Science) version 25.0. This study obtained the results of multiple linear regression analysis Y = 8.962 + 0.431X1 + 0.461X2 which shows that room prices and facilities positively affect guest decisions to stay at The Aveda Boutique Hotel. The t-test results show t-count room price 3.021 and t-count facilities 4.124> t table 1.666, which means the hypothesis is accepted. Then the F test results show Fcount 29.548> Ftable 3.123, which means the hypothesis is accepted. From the results of the T test and F test analysis, it can be concluded that room prices and facilities significantly affect both partially and simultaneously guest decisions to stay at The Aveda Boutique Hotel. The coefficient of determination test results shows that the effect of room prices and facilities is 45.1% on guest stay decisions, while other variables outside this study influence the remaining 54.9%. In this study, the most dominant variable influencing guest decisions to stay in facilities with a value of 0.437. Keywords: Room rates, Facilities, the guest's decision to stay Keywords: Room rates, Facilities, the guest's decision to stay